Characteristics of Donuts with Variations in Soy Flour Substitution (Glycine max L.) and Fermentation Time: Karakteristik Donat dengan Variasi Substitusi Tepung Kedelai (Glycine max L.) Serta Lama Fermentasi - Ayu Mei Wulansari; Akhmad Mustofa; Merkuria Karyantina (Agrobiotek, 2024)
Donuts are foods made from high protein wheat flour, in this study donuts were made from substitution of wheat flour and soybean flour. This study aims to determine the effect of soy flour substitution (Glycine max L.) and of determine fermentation time of (60, 75 and 90 min) on soy flour donuts which have the highest protein content and panelists' favorite. Complete Rendomized Design (RAL) Faktorial with two factors used in this research. The first factor was is the ratio of wheat flour and soy flour (95;5, 90;10, 85;15) . The second factor was is the variation of fermentation time (60, 75, 90 min). It was determined for protein, ash , water, fat , reducing sugar, total carbohydrates, and organoleptic. The data was determined Analysis using of Variance (ANOVA). The results showed that donuts with the addition of soy flour and fermentation time had a significant effect (Î±<0.05) on protein content, sugar content, flavor and overall preference. The best treatment of soybean flour donuts based on chemical and organoleptic tests, namely the ratio of wheat flour and soybean flour (85:15) using 90 minutes of fermentation. Soy flour donuts with the best treatment had a 20.30% of moisture; 1.77% ash content; protein content 10.38%; reducing sugar content 22.52%; total carbohydrates 49.51%; color dark brown 3.25; unpleasant flavor 2.95; savory taste 3.01 and very liked overall favorite 3,57.